Mental bases of modern Russian society socio-political development - a, Alexey G. Ivanov, Oksana P. Chernykh, Yuriy D. Korobkov,Svetlana S. Velikanov, Irina V. Samarokova, Natalia. Kozhushkov (Opción, 2019)
The article compares the historical material and the data of modern sociological surveys through historical and genetic methods. Its result was the conclusion that the socio-psychological basis of the modern Russian political process is such features as patience, the reverse side of which can be various social conflicts by form and strength; such features of a Russian man state consciousness as the weave of state and anarchic principles. As a conclusion, the article shows the need to grow the basic features of truly Russian consciousness, relying on the common in the mental development of mankind.